2015
DOI: 10.3390/rs70708757
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Vegetation Recovery in the Damage Area of Wenchuan Earthquake Using MODIS Data

Abstract: Abstract:The catastrophic 8.0 Richter magnitude earthquake that occurred on 12 May 2008 in Wenchuan, China caused extensive damage to vegetation due to widespread landslides and debris flows. In the past five years, the Chinese government has implemented a series of measures to restore the vegetation in the severely afflicted area. How is the vegetation recovering? It is necessary and important to evaluate the vegetation recovery effect in earthquake-stricken areas. Based on MODIS NDVI data from 2005 to 2013, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 26 publications
6
18
1
Order By: Relevance
“…For example, Chen et al estimated 20.7% forest destroyed by Wenchuan earthquake using InSAR tools [16]; Jiang et al found only 13.8% of forests was affected according to a quantified threshold based on MODIS NDVI data [17]. In this study, we suggested the fraction of impacted forest areas was 33.4%, which was in good agreement with our field experience.…”
Section: Improvement Of the Synthetic Approach In Earthquake Influencsupporting
confidence: 88%
See 4 more Smart Citations
“…For example, Chen et al estimated 20.7% forest destroyed by Wenchuan earthquake using InSAR tools [16]; Jiang et al found only 13.8% of forests was affected according to a quantified threshold based on MODIS NDVI data [17]. In this study, we suggested the fraction of impacted forest areas was 33.4%, which was in good agreement with our field experience.…”
Section: Improvement Of the Synthetic Approach In Earthquake Influencsupporting
confidence: 88%
“…This outline is consistent with the spatial pattern of landslides triggered by the Wenchuan earthquake, which declined with distance away from the epicenter until about 80 km from the surface rupture [29]. The new Wenchuan impact boundary outlined in this study greatly improved the accuracy of the earthquake impact assessment compared with previous studies that used jurisdiction boundaries alone [15][16][17]. Using jurisdiction boundary can significantly deviate the estimation of the earthquake effects.…”
Section: Improvement Of the Synthetic Approach In Earthquake Influencsupporting
confidence: 80%
See 3 more Smart Citations